Brain Alterations and Clinical Symptoms of Dementia in Diabetes: Aβ/Tau-Dependent and Independent Mechanisms - Sato, Naoyuki; Morishita, Ryuichi (Frontiers in Endocrinology, 2014)
Emerging evidence suggests that diabetes affects cognitive function and increases the incidence of dementia. However, the mechanisms by which diabetes modifies cognitive function still remains unclear. Morphologically, diabetes is associated with neuronal loss in the frontal and temporal lobes including the hippocampus, and aberrant functional connectivity of the posterior cingulate cortex and medial frontal/temporal gyrus. Clinically, diabetic patients show decreased executive function, information processing, planning, visuospatial construction, and visual memory. Therefore, in comparison with the characteristics of AD brain structure and cognition, diabetes seems to affect cognitive function through not only simple AD pathological feature-dependent mechanisms, but also independent mechanisms. As an Abeta/tau-independent mechanism, diabetes compromises cerebrovascular function, increases subcortical infarction and might alter the blood brain barrier (BBB). Diabetes also affects glucose metabolism, insulin signaling and mitochondrial function in the brain. Diabetes also modifies metabolism of Abeta and tau and causes Abeta/tau-dependent pathological changes. Moreover, there is evidence that suggests an interaction between Abeta/tau-dependent and independent mechanisms. Therefore, diabetes modifies cognitive function through Abeta/tau-dependent and independent mechanisms. Interaction between these two mechanisms forms a vicious cycle.